The Role of Probiotic Lactic Acid Bacteria and Bifidobacteria in the Prevention and Treatment of Inflammatory Bowel Disease and Other Related Diseases: A Systematic Review of Randomized Human Clinical Trials - Gil, Angel; Plaza-Diaz, Julio; Gomez-Llorente, Carolina; Saez-Lara, Maria Jose (BioMed research international, 2015)
Inflammatory bowel disease (IBD), which includes Crohn’s disease (CD) and ulcerative colitis (UC), is a chronic inflammation of the small intestine and colon caused by a dysregulated immune response to host intestinal microbiota in genetically susceptible subjects. A number of fermented dairy products contain lactic acid bacteria (LAB) and bifidobacteria, some of which have been characterized as probiotics that can modify the gut microbiota and may be beneficial for the treatment and the prevention of IBD. The objective of this review was to carry out a systematic search of LAB and bifidobacteria probiotics and IBD, using the PubMed and Scopus databases, defined by a specific equation using MeSH terms and limited to human clinical trials. The use of probiotics and/or synbiotics has positive effects in the treatment and maintenance of UC, whereas in CD clear effectiveness has only been shown for synbiotics. Furthermore, in other associated IBD pathologies, such as pouchitis and cholangitis, LAB and bifidobacteria probiotics can provide a benefit through the improvement of clinical symptoms. However, more studies are needed to understand their mechanisms of action and in this way to understand the effect of probiotics prior to their use as coadjuvants in the therapy and prevention of IBD conditions.